A study on conceptual metaphor of “dream” in English and Vietnamese songs”. - Châu Ngọc Thạch Anh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The aim of this study is to examine the conceptual metaphor of “dream” in English and Vietnamese songs in the light of cognitive linguistics. It also discovers and explains the similarities and differences of conceptual metaphors of “dream” in English and Vietnamese song. Also, this study will be a useful reference for those who are interested in conceptual metaphors in song